Inclusion of disability‐related content in nurse practitioner curricula. Issue 4 (20th June 2014) - Smeltzer, Suzanne C.; Blunt, Elizabeth; Marozsan, Heather; Wetzel‐Effinger, Lisa
Abstract Purpose To examine the integration of disability‐content in a national sample of nurse practitioner curricula. Data sources Responses of National Organization of Nurse Practitioner Faculties (NONPF) members to an online 34‐item survey designed to assess disability‐related content included in nurse practitioner (NP) curricula; populations of people with disabilities addressed; models of disability; and resources used to teach about disability, facilitators and barriers to inclusion of disability, and respondents' assessment of the adequacy of coverage of disability in their programs. A survey used previously to assess integration of disability content in undergraduate nursing programs was modified to make it relevant to NP curricula. Nursing faculty and people with disability validated the survey to ensure its completeness and sensitivity to the disability community. Participating programs represent 111 (33.6%) NP programs. Conclusions Lack of disability‐related content reported by NP faculty in the majority of programs suggests that there is considerable room for improvement in efforts to address this often vulnerable population. Because people with disabilities can be found in any setting where health care is provided, all NPs need to be prepared to care for people with disabilities across the life span. Implications for practice Strategies need to be developed and implemented to increase the awareness of NP faculty about the health issues of people with disabilities and integration of disability‐related content without disrupting existing overloaded NP curricula.